N‐dihydrogalactochitosan as a potent immune activator for dendritic cells. Issue 4 (10th January 2017) - El‐Hussein, Ahmed; Lam, Samuel S. K.; Raker, Joseph; Chen, Wei R.; Hamblin, Michael R.
Abstract: Immunotherapy has become one of the fastest growing areas of cancer research. A promising in situ autologous cancer vaccine (inCVAX) uses a novel immune activator, N ‐dihydrogalactochitosan (GC), that possesses the ability to stimulate dendritic cells (DC). inCVAX is a combination treatment procedure involving treatment of the tumor with a thermal near‐infrared laser to liberate whole cell tumor antigens, followed by injection of GC (a glucosamine polymer with galactose attached to the amino groups) into the treated tumor thereby inducing a systemic antitumor immune response. Regression of both the treated tumor and distant untreated metastases has been observed in both nonclinical and clinical settings following inCVAX. We studied the stimulatory action of GC on relatively immature DCs (DC2.4 cell line) in vitro . GC at 1 mg/mL was a potent stimulator for DC with limited toxicity, giving increased expression of major histocompatibility complex class 2, CD80, and CD11c. Confocal imaging also revealed qualitatively increased uptake of antigen (Texas red‐labeled ovalbumin) by DCs after the introduction of GC. To visualize cellular uptake, GC was conjugated with FITC‐fluorophore revealing its cellular internalization after 8 hours. In some cases GC was more effective than the toxic TLR4 agonist, lipopolysaccharide. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 963–972, 2017.